Discussion: Observations from Cyclic Tests on Deep, Wide-Flange Beam-Columns - Maison, Bruce F. (Engineering Journal, 2019)
Discussion paper on "Observations from Cyclic Tests on Deep, Wide-Flange Beam-Columns" (paper 2015-16) by Gulen Ozkula, John Harris, and Chia-Ming Uang published EJ 2017 1st Quarter.